Assessment of the Psychometric Properties of the Attitude Scale for Nursing Profession (ASNP) - Zainab Rahimi; Maryam Radmehr; Fahime Kashani (Hamadan University of Medical Sciences, 2023)
Background and Objective: The attitude towards the nursing profession is one of the most important topics in all areas of care provision from the time of choosing this profession to the end of the service period. The present study was conducted to determine the psychometric indicators of the Attitude Scale for the Nursing Profession (ASNP). Materials and Methods: This descriptive methodological study initially obtained permission from the original author to use the tool. The sample included 301 nurses who were selected using the convenience sampling method and working at hospitals affiliated with the Golestan University of Medical Sciences. Following that, the Attitude Scale for Nursing Profession (ASNP) developed by Ipek and Coban was translated into the Persian language according to the International Quality of Life Assessment (IQOLA) protocol. The validity assessment of the scale was carried out using a quantitative and qualitative method based on content validity (Content Validity Ratio [CVR] and Content Validity Index [CVI]) and utilizing the opinions of 11 nursing experts. Moreover, reliability was evaluated by two methods of internal consistency (Cronbach's alpha), test-retest, and the intra-class correlation coefficient (ICC). Data analysis was conducted using exploratory and confirmatory factor analysis in SPSS (version 22) and AMOS (version 23) software. Results: In the current study, the CVR score of the entire questionnaire was calculated as 0.72; however, statements 16 and 19 scored less than the acceptable level; therefore, they did not have proper validity and were removed. The CVI of all items was more than 0.79. The Cronbach's alpha coefficient of ASNP was obtained at 0.96. The ICC was determined at 0.93, and the stability reliability in the two stages of the test-retest method was 0.789 (P=0.001). The results of exploratory factor analysis showed that the Persian version of the scale has a 3-factor structure (characteristics of the nursing profession, preference for the nursing profession, and the general position of the nursing profession). These factors were confirmed by confirmatory factor analysis. (RMSEA=0.092, AGFA=0.90, and GFI=0.93). The estimation of standard factor loadings in confirmatory factor analysis showed that this scale has an acceptable fit in Iranian culture and has good construct validit. Conclusion: The results showed that the ASNP has the necessary validity and reliability after removing two items and can be used as a comprehensive and reliable tool to investigate the attitude towards the nursing profession in Iran.